Evaluation a training intervention for injury prevention knowledge of children with physical disabilities among special educators in Indonesia - Setia Budi Budi; Mega iswari; Damri Damri; Alan Rahman Rendra (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Teachers working with students with disabilities play a critical role in maintaining safe learning environments, yet structured training in school-based injury prevention remains limited in Indonesia. This study evaluated a school-based training intervention designed to enhance special educators’ injury prevention knowledge. A quasi-experimental pretest–posttest control group design was employed involving 156 special education teachers in West Sumatra, Indonesia (intervention n = 78; control n = 78). Participants completed a self-report questionnaire assessing injury prevention knowledge, attitudes, and perceived skills before and after the intervention. The intervention consisted of structured workshops, guided practice, and follow-up mentoring delivered over 12 weeks. Paired-samples t-tests indicated a significant increase in injury prevention knowledge scores in the intervention group compared to baseline (p < .001), while no significant change was observed in the control group. Analysis of covariance (ANCOVA), controlling for pretest scores, showed a significant group effect at post-test (p < .001), indicating higher adjusted post-test scores among teachers who received the training. Improvements were also observed in self-reported attitudes and perceived skills. These findings suggest that structured training interventions may enhance special educators’ self-reported injury prevention knowledge in the Indonesian context. The study contributes to the growing literature on professional development in special education and highlights the need for systematic safety-focused training for teachers working with students with disabilities.